Hydrocarbon resin polymers, methods for making same, and compositions and substrates containing same

By introducing bridge ring units, unit pyridinol-based units and dipyridinol-based units into the hydrogenated carbon resin polymer, the unit content and structure are adjusted, and the problem of high dielectric loss in high-frequency band 5G signal transmission is solved, and the polymer still maintains excellent electrical and thermal properties after high temperature treatment.

JP7661392B2Active Publication Date: 2025-04-14LEE CHANG YUNG CHEM IND CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023065872
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-19
Filing Date
2023-04-13
Publication Date
2025-04-14
Estimated Expiration
2043-04-13

AI Technical Summary

Technical Problem

In the existing high-frequency 5G signal transmission, the dielectric loss of the packaging material is relatively high, which affects the signal quality. The hydrogenated carbon resin is prone to oxidation during processing, resulting in an increase in the dielectric constant and loss factor and reducing electrical performance.

Method used

A hydrogenated carbon resin polymer containing bridge ring units, unit pyridinol-based units and dipyridinol-based units is used to adjust the content and structure of the unit to improve the glass transition temperature and electrical properties of the polymer and reduce dielectric loss.

Benefits of technology

It realizes that the polymer still maintains excellent electrical and thermal properties after high temperature treatment, reduces dielectric loss and improves the quality of signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661392000031
    Figure 0007661392000031
  • Figure 0007661392000001
    Figure 0007661392000001
  • Figure 0007661392000002
    Figure 0007661392000002
Patent Text Reader

Abstract

To provide a hydrocarbon resin polymer having superior thermal properties, solubility, processability, cost-effectiveness, and / or electrical performance, and a preparation method thereof, and a composition and a substrate each comprising the same.SOLUTION: A hydrocarbon resin polymer is provided. The hydrocarbon resin polymer includes: 0.15-15 mol% of repeating units (A), which are derived from bridged ring monomer compounds; 15-90 mol% of repeating units (B), which are derived from monovinyl aromatic compounds; and 8-80 mol% of repeating units (C), which are derived from divinyl aromatic compounds.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin polymer, a method for producing the same, and a composition and a substrate containing the same, and in particular to a hydrocarbon resin polymer, a method for producing the same, and a composition and a substrate containing the same. [Background technology]

[0002] Fifth generation mobile networks (5G mobile communications) is the latest mobile communications technology. 5G mobile communications are characterized by high-speed transmission, multiple simultaneous connections, and low latency. Currently, 5G mobile communications are divided into three types according to the band used: high-band 5G, mid-band 5G, and low-band 5G.

[0003] High-band 5G can provide a very high connection rate. However, in the transmission process of high-band 5G, the quality of signal transmission and reception is affected by the high-frequency band path loss, conductor loss, and dielectric loss. The dielectric loss is directly related to the packaging material. Therefore, it is necessary to develop packaging materials with low dielectric loss to reduce the dielectric loss in the transmission process of high-band 5G, and thus improve the quality of signal transmission and reception.

[0004] The goal of reducing dielectric loss can be achieved by lowering the dielectric properties (dielectric constant (Dk) and dielectric loss tangent (Df)) of the packaging material. Hydrocarbon resin or polyolefin materials, which are made of hydrocarbon atoms, have low dielectric loss properties due to their low number of polar functional groups. However, during processing, hydrocarbon resins are easily oxidized by the heating process, and after oxidation, the electrical performance of the hydrocarbon resins decreases (i.e., the dielectric constant and dielectric loss tangent increase). Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above problems, the present disclosure provides a hydrocarbon resin polymer having excellent thermal properties (high glass transition temperature (Tg)), solubility, processability, cost-effectiveness, and / or electrical performance. The hydrocarbon resin polymer of the present disclosure can maintain excellent electrical performance and / or excellent thermal performance even after undergoing a heating process. That is, the hydrocarbon resin polymer of the present disclosure has excellent thermal stability. [Means for solving the problem]

[0006] In some embodiments, the present disclosure provides a hydrocarbon resin polymer comprising 0.15 to 15 mol % of repeat units (A) derived from a bridged ring monomer compound, 15 to 90 mol % of repeat units (B) derived from a monovinyl aromatic compound, and 8 to 80 mol % of repeat units (C) derived from a divinyl aromatic compound.

[0007] In some embodiments, the present disclosure provides a method of making a hydrocarbon resin polymer, the method including the steps of providing 15-50 mol % of a bridged ring monomer compound, providing 38-80 mol % of a monovinyl aromatic compound, providing 2-45 mol % of a divinylaromatic compound, and polymerizing the bridged ring monomer compound, the monovinyl aromatic compound, and the divinylaromatic compound to form the hydrocarbon resin polymer.

[0008] In some embodiments, the present disclosure provides a resin composition comprising a hydrocarbon resin polymer comprising 0.15-15 mol % of repeating units (A) derived from a bridged ring monomer compound, 15-90 mol % of repeating units (B) derived from a monovinyl aromatic compound, and 8-80 mol % of repeating units (C) derived from a divinyl aromatic compound.

[0009] In some embodiments, the present disclosure provides a substrate comprising a hydrocarbon resin polymer comprising 0.15-15 mol % of repeat units (A) derived from a bridged ring monomer compound, 15-90 mol % of repeat units (B) derived from a monovinyl aromatic compound, and 8-80 mol % of repeat units (C) derived from a divinyl aromatic compound. [Brief description of the drawings]

[0010] In order to make the objectives, features and advantages of the present disclosure more apparent and understandable, specific embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings. [Figure 1] FIG. 1 is a schematic diagram of a substrate according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] It will be understood that when "comprises" and / or "comprises" are used herein, they indicate the presence of a referred feature, integer, step, operation, element, ingredient, and / or group thereof, but do not exclude the presence or increase of one or more other features, integers, steps, operations, elements, ingredients, and / or groups thereof. When the singular form "a" is used herein, the plural form is also intended to be included unless the context clearly indicates otherwise.

[0012] It will be understood that, although terms such as "first," "second," and the like are used herein to describe respective elements, components, regions, layers, and / or sections, these elements, components, regions, layers, and / or sections are not limited by these terms, but are merely used to distinguish one element, component, region, layer, and / or section from another element, component, region, layer, and / or section.

[0013] In the present specification, the terms "about", "approximately", and "approximately" generally mean within 20%, preferably within 10%, more preferably within 5%, or within 3%, or within 2%, or within 1%, or within 0.5% of a given value or range. Here, a given number is an approximate number, that is, even if there is no specific description of "about", "approximately", or "approximately", it may include the meaning of "about", "approximately", or "approximately". Furthermore, it will be understood that the numerical values ​​displayed in the present disclosure may include the numerical values ​​and deviation values ​​within the range of deviation that is acceptable to a person of ordinary skill in the field. It will also be understood that the notation "a to b" used to express a specific numerical range in the present specification is defined as "≧a and ≦b".

[0014] Unless otherwise defined, all terms (including technical and scientific terms) used in the present specification have the same meaning as those commonly understood by those skilled in the art. These terms are, for example, terms defined in commonly used dictionaries, and should be interpreted to have a meaning consistent with the relevant technology and the background or context of this application, and should not be interpreted in an idealized or overly strict manner unless otherwise defined in this disclosure. Below, descriptions that may unnecessarily misinterpret known effects and structures in this disclosure are omitted.

[0015] In this disclosure, 1-20 "Alkyl group" refers to a monovalent group of straight, branched, or cyclic aliphatic hydrocarbons having from 1 to 20 carbon atoms in the carbon chain. 1-20 Non-limiting examples of alkyl groups include, but are not limited to, methyl, ethyl, propyl, isobutyl, sec-butyl, tert-butyl, pentyl, isoamyl, hexyl, decyl, dodecyl, cyclohexyl, cyclooctyl, and cyclododecyl alkyl groups.

[0016] In this disclosure, 2-20The term "alkenyl group" refers to a monovalent group of straight, branched, or cyclic aliphatic hydrocarbons having from 2 to 20 carbon atoms in the carbon chain and at least one carbon-carbon double bond. 2-20 Non-limiting examples of alkenyl groups include, but are not limited to, ethenyl, propenyl, isobutenyl, sec-butenyl, tert-butenyl, pentenyl, isopentenyl, hexenyl, decenyl, dodecenyl, pentadecenyl, cyclohexenyl, cyclooctenyl, cyclopentenyl, cyclopentadienyl, and cyclopentadecenyl groups.

[0017] In this disclosure, 1-20 The term "carboxylate group having an alkyl chain" refers to a group having the following structure:

[0018] [ka]

[0019] In the formula, "*" represents a site for linking to other groups, and R 1 is C 1-20 is an alkyl group, R 2 is a single bond or C 1-20 is an alkyl group, and R 1 and R 2 The total number of carbon atoms in the carbon backbone of the alkyl group is 1 to 20.

[0020] Some embodiments of the present disclosure provide a hydrocarbon resin polymer comprising 0.15 to 15 mole fraction (mol %) of a repeating unit (A) derived from a bridged ring monomer compound, 15 to 90 mol % of a repeating unit (B) derived from a monovinyl aromatic compound, and 8 to 80 mol % of a repeating unit (C) derived from a divinyl aromatic compound.

[0021] Here, the bridged ring monomer compound refers to a compound that contains a bridged ring structure and can be polymerized with the same or different other compound to form a polymer. The bridged ring structure refers to a structure that contains at least two carbon rings and shares two carbon atoms that are not directly connected. In some embodiments, the bridged ring structure in the bridged ring monomer compound can contain 3 to 12 ring atoms and 1 to 2 double bonds. In some embodiments, the bridged ring structure can be unsubstituted. In some embodiments, at least one hydrogen atom in the bridged ring structure is selected from the group consisting of C 1-20 Alkyl group, C 2-20 Alkenyl group, or C 1-20 In some embodiments, the bridged ring structure has at least two substituents, and the at least two substituents are selected from the group consisting of a carboxylate group having an alkyl chain. 1-20 Alkyl group, C 2-20 Alkenyl group, or C 1-20 The two or more substituents may be any two or more selected from the group consisting of carboxylate groups having alkyl chains. Among these at least two substituents, adjacent substituents may form a ring. Examples of bridged ring monomer compounds may include norbornene (NB), dicyclopentadiene (DCPD), dicycloheptadiene (NBD), 2-acetyl-5-norbornene, methyl 5-norbornene-2-carboxylate, vinyl norbornene, and ethylidene-norbornene, but the present disclosure is not limited thereto.

[0022] Dicyclopentadiene (DCPD)

[0023] [ka]

[0024] Ethylidene-norbornene

[0025] [ka]

[0026] Dicycloheptadiene (NBD)

[0027] [ka]

[0028] Vinyl norbornene

[0029] [ka]

[0030] Methyl 5-norbornene-2-carboxylate

[0031] [ka]

[0032] Norbornene (NB)

[0033] [ka]

[0034] 2-acetyl-5-norbornene [ka]

[0035] The repeating unit (A) derived from the bridged ring monomer compound contains a bridged ring structure from the bridged ring monomer compound. Thus, the repeating unit (A) may contain a bridged ring structure having 3 to 12 ring atoms and 0 to 1 double bond. In some embodiments, the repeating unit (A) may have any of the following structures, but the present disclosure is not limited thereto.

[0036] [ka]

[0037] The "*" in the above structure represents a site for linking to other groups. Compared with linear repeat units, the repeat unit (A) having a bridged ring structure has higher rigidity, and therefore can increase the glass transition temperature or thermal performance of the hydrocarbon resin polymer. If the content of the repeat unit (A) in the hydrocarbon resin polymer is too low, for example less than 0.5 mol%, the hydrocarbon resin polymer cannot have the required thermal performance. If the content of the repeat unit (A) in the hydrocarbon resin polymer is too high, for example higher than 15 mol%, the cost-effectiveness of the hydrocarbon resin polymer decreases. In some embodiments, the hydrocarbon resin polymer of the present disclosure may contain 1 to 14 mol%, 2 to 13 mol%, 3 to 12 mol%, 4 to 10 mol%, or 6 to 8 mol% of the repeat unit (A). In some embodiments, the hydrocarbon resin polymer of the present disclosure may contain 5 mol%, 7 mol%, or 9 mol% of the repeat unit (A).

[0038] Here, the term "monovinylaromatic compound" refers to a compound that contains a carbocyclic aromatic structure and in which one hydrogen atom on a ring carbon atom of the carbocyclic aromatic structure is replaced with a vinyl group. In some embodiments, the vinyl group may be unsubstituted. In some embodiments, at least one hydrogen atom on the vinyl group is replaced with a C 1-20In some embodiments, the carbocyclic aromatic structure may be unsubstituted. In some embodiments, at least one hydrogen on a ring carbon atom in the carbocyclic aromatic structure is selected from the group consisting of C 1-20 Examples of monovinyl aromatic compounds may include, but are not limited to, styrene, methylstyrene, or ethylstyrene.

[0039] The repeat unit (B) derived from the monovinyl aromatic compound may include a carbocyclic aromatic structure from the monovinyl aromatic compound. For example, in some embodiments, the repeat unit (B) may have any of the following structures, but the present disclosure is not limited thereto.

[0040] [ka]

[0041] The "*" in the above structure represents a site that is linked to other groups. The repeating unit (B) can increase the solubility of the hydrocarbon resin polymer in a solvent such as toluene. If the content of the repeating unit (B) in the hydrocarbon resin polymer is too low, for example less than 15 mol%, the solubility of the hydrocarbon resin polymer in a solvent is poor. If the content of the repeating unit (B) in the hydrocarbon resin polymer is too high, for example more than 90 mol%, other performances of the hydrocarbon resin polymer, such as thermal performance, may be reduced. In some embodiments, the hydrocarbon resin polymer of the present disclosure may contain 20 to 90 mol%, 25 to 85 mol%, 30 to 80 mol%, 35 to 75 mol%, 40 to 70 mol%, or 45 to 65 mol% of the repeating unit (B). In some embodiments, the hydrocarbon resin polymer of the present disclosure may contain 50 mol%, 55 mol%, or 60 mol% of the repeating unit (B).

[0042] Here, the term "divinylaromatic compound" refers to a compound that contains a carbocyclic aromatic structure and has two hydrogen atoms on the ring carbon atoms of the carbocyclic aromatic structure replaced with vinyl groups. In some embodiments, the vinyl group may be unsubstituted. In some embodiments, at least one hydrogen atom in the vinyl group is C 1-20 In some embodiments, the carbocyclic aromatic structure may be unsubstituted. In some embodiments, at least one hydrogen on a ring carbon atom in the carbocyclic aromatic structure is C 1-20 Examples of divinylaromatic compounds may include, but are not limited to, divinylbenzene.

[0043] The repeating unit (C) derived from the divinylaromatic compound comprises a carbon ring aromatic structure from the divinylaromatic compound. In some embodiments, the repeating unit (C) may comprise a bridging unit and a non-bridging unit. In some embodiments, the repeating unit (C) may comprise the following bridging unit, but the present disclosure is not limited thereto.

[0044] [ka]

[0045] In some embodiments, the repeat unit (C) can include the following non-bridging units, although the disclosure is not limited thereto:

[0046] [ka]

[0047] In the above structure, "*" represents a site for linking to other groups.

[0048] The degree of crosslinking of the repeating unit (C) is calculated by the following formula.

[0049]

number

[0050] In some embodiments, the crosslinking degree of the repeating unit (C) is 0.2 to 0.6. If the crosslinking degree of the repeating unit (C) is too low, for example, less than 0.2, the crosslinking degree of the hydrocarbon resin polymer is low and the thermal performance and / or electrical performance are poor. If the crosslinking degree of the repeating unit (C) is too high, for example, higher than 0.6, the processability of the hydrocarbon resin polymer is reduced. The repeating unit (C) can increase the crosslinking degree of the hydrocarbon resin polymer. The higher the crosslinking degree of the hydrocarbon resin polymer, the better the thermal performance, thermal stability, and / or electrical performance of the hydrocarbon resin polymer. If the content of the repeating unit (C) in the hydrocarbon resin polymer is too low, for example, less than 8 mol%, the crosslinking degree of the hydrocarbon resin polymer is low and the thermal performance and / or electrical performance are poor. If the content of the repeating unit (C) in the hydrocarbon resin polymer is too high, for example, higher than 80 mol%, the processability of the hydrocarbon resin polymer is reduced. In some embodiments, the hydrocarbon resin polymer of the present disclosure may include 10-80 mol%, 10-75 mol%, 15-75 mol%, 20-70 mol%, 25-65 mol%, 30-60 mol%, or 35-55 mol% of repeating units (C). In some embodiments, the hydrocarbon resin polymer of the present disclosure may include 40 mol%, 45 mol%, or 40 mol% of repeating units (C). In some embodiments, the sum of the repeating units (A) and the repeating units (C) is 13 mol% or more. As mentioned above, both the repeating units (A) and the repeating units (C) affect the thermal performance and thermal stability of the hydrocarbon resin polymer. The present inventors have found that when the sum of the repeating units (A) and the repeating units (C) is 13 mol% or more, the hydrocarbon resin polymer can be provided with excellent thermal performance and thermal stability.

[0051] In some embodiments, the hydrocarbon resin polymer may include a reactive double bond. In this disclosure, a "reactive double bond" refers to a double bond in the repeat unit (A) or the repeat unit (C) that can undergo a reaction with another compound or polymer. For example, in some embodiments, the reactive double bond includes any of the double bonds in the repeat unit (A) shown below:

[0052] [ka]

[0053] Alternatively, the reactive double bond may include a double bond that is not in a benzene ring in the repeat unit (C) shown below.

[0054] [ka]

[0055] However, the present disclosure is not limited to the above.

[0056] In some embodiments, the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer is less than 10%. If the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer is too high, for example, higher than 10%, the hydrocarbon resin polymer is easily oxidized during the heating process, which leads to a decrease in the electrical performance of the hydrocarbon resin polymer. In some embodiments, the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer is higher than 2.2%. If the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer is too low, for example, less than 2.2%, the peel strength of the layer containing the hydrocarbon resin polymer is excessively low. In some embodiments, the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer can be 2.2% to 10%, 2.5% to 10%, 2.8% to 9%, or 3% to 8%. When the content of the reactive double bonds in the hydrocarbon resin polymer is within the above range, the hydrocarbon resin polymer is less likely to oxidize in a high temperature environment (for example, 150° C. or higher), or the crosslinking reaction tends to be completed before oxidation, thereby improving the electrical performance of the hydrocarbon resin polymer. In some embodiments, the number average molecular weight (Mn) of the hydrocarbon resin polymer may be 2,500 to 10,000 g / mol. If the number average molecular weight of the hydrocarbon resin polymer is too high, the solubility of the hydrocarbon resin polymer decreases.

[0057] The hydrocarbon resin polymer of the present disclosure having the above-mentioned characteristics has excellent thermal performance, thermal stability, and / or electrical performance. For example, in some embodiments, the hydrocarbon resin polymer of the present disclosure has a glass transition temperature higher than about 100° C., a dielectric constant (Dk) less than about 3.4, a dielectric loss tangent (Df) less than about 0.0030, and the change in the dielectric constant and / or dielectric loss tangent before and after the heating process is not large, and / or the dielectric loss tangent after the heating process is less than about 0.0020. In addition, the hydrocarbon resin polymer of the present disclosure also has excellent solubility and / or processability, and can be easily dissolved in a solvent to prepare a resin composition with excellent thermal performance, thermal stability, electrical performance, and / or processability.

[0058] The present disclosure further provides a resin composition comprising the above-mentioned hydrocarbon resin polymer. In some embodiments, the resin composition may further comprise other hydrocarbon resin polymers. Here, the other hydrocarbon resin polymers refer to any well-known hydrocarbon resin polymers other than the hydrocarbon resin polymers shown in the present disclosure. In some embodiments, the resin composition may further comprise other resin polymers. Here, the other resin polymers refer to resin polymers that are not hydrocarbon resin polymers. Examples of other resin polymers may include polyphenylene ether resins, polycarbonate resins, acrylic resins, epoxy resins, polyurethane resins, or any combination thereof, but the present disclosure is not limited thereto. In some embodiments, the weight ratio of the hydrocarbon resin polymer to the other resin polymers in the resin composition may be 100 to 1: 0 to 99. In some embodiments, the weight ratio of the total of the hydrocarbon resin polymer and the other hydrocarbon resin polymers in the resin composition to the other resin polymers may be 100 to 1: 0 to 99. That is, (hydrocarbon resin polymer + other hydrocarbon resin polymer): other resin polymer may be 100 to 1: 0 to 99 by weight.

[0059] In some embodiments, the resin composition of the present disclosure further comprises a solvent capable of dissolving the hydrocarbon resin polymer and / or other resin polymers. In some embodiments, the solvent is toluene. In some embodiments, the resin composition may comprise 80 to 100 parts by weight, 90 to 100 parts by weight, or 95 to 100 parts by weight of the solvent per 100 parts by weight of the total weight of the hydrocarbon resin polymer and other resin polymers (i.e., when the resin composition does not contain other resin polymers, the weight of the hydrocarbon resin polymer is taken as 100 parts by weight).

[0060] In some embodiments, the resin composition further comprises an initiator and / or a crosslinking agent. In some embodiments, the resin composition may comprise 0.1 to 5 parts by weight, 0.1 to 4 parts by weight, 0.1 to 3 parts by weight, 0.1 to 2 parts by weight, 0.1 to 1 part by weight, 0.1 to 0.5 parts by weight, 0.2 to 0.4 parts by weight, 0.3 to 0.4 parts by weight, or 0.3 to 0.35 parts by weight of the initiator, based on 100 parts by weight of the total weight of the hydrocarbon resin polymer and other resin polymers. In some embodiments, the resin composition may comprise 10 to 50 parts by weight, 12 to 40 parts by weight, or 15 to 35 parts by weight of the crosslinking agent, based on 100 parts by weight of the total weight of the hydrocarbon resin polymer and other resin polymers.

[0061] In some embodiments, the resin composition may further include one or more additives. That is, in addition to the hydrocarbon resin polymer and other resin polymers, in some embodiments, the resin composition may include an initiator, a crosslinker, an additive, or any combination thereof. In some embodiments, the resin composition may include 10 to 100 parts by weight, 15 to 85 parts by weight, or 25 to 55 parts by weight of the additive, based on 100 parts by weight of the total weight of the hydrocarbon resin polymer and other resin polymers. Examples of additives may include toughening agents, fillers, and / or photosensitizers, but the present disclosure is not limited thereto.

[0062] The hydrocarbon resin polymer of the present disclosure has excellent thermal performance, thermal stability, electrical performance, solubility and / or processability, and is therefore applicable to the fabrication of substrates, and the substrates comprising the hydrocarbon resin polymer also have excellent thermal performance, thermal stability and / or electrical performance.

[0063] The present disclosure further provides a substrate comprising a hydrocarbon resin polymer or a combination of a hydrocarbon resin polymer and another resin polymer. In some embodiments, the hydrocarbon resin polymer may comprise the above-mentioned hydrocarbon resin polymer. In some embodiments, the hydrocarbon resin polymer may further comprise another hydrocarbon resin polymer. Here, the other hydrocarbon resin polymer refers to any well-known hydrocarbon resin polymer other than the hydrocarbon resin polymers listed in the present disclosure. Here, the other resin polymer refers to a resin polymer that is not a hydrocarbon resin polymer. Examples of the other resin polymer may include polyphenylene ether resin, polycarbonate resin, acrylic resin, epoxy resin, and polyurethane resin, but the present disclosure is not limited thereto. In some embodiments, the weight ratio of the hydrocarbon resin polymer to the other resin polymer may be 100-1:0-99. In some embodiments, the weight ratio of the total of the hydrocarbon resin polymer and the other hydrocarbon resin polymer to the other resin polymer may be 100-1:0-99.

[0064] 1 is a schematic diagram of a substrate 10 according to one embodiment of the present disclosure. As shown in FIG. 1, the substrate 10 includes a base 101, a polymer layer 103 disposed above the base 101, and an adhesive layer 105 disposed between the base 101 and the polymer layer 103. The adhesive layer 105 connects the base 101 and the polymer layer 103.

[0065] In some embodiments, the base 101 may include a metal layer. In some embodiments, the base 101 may include a copper foil. In some embodiments, the polymer layer 103 includes the hydrocarbon resin polymers described above or a combination of hydrocarbon resin polymers and other resin polymers. In some embodiments, the adhesive layer 105 may include any material capable of connecting the base 101 and the polymer layer 103. In some embodiments, the adhesive layer 105 may include a silane adhesive.

[0066] The present disclosure further provides a method for making a hydrocarbon resin polymer, comprising the steps of: preparing 15-50 mol % of a bridged ring monomer compound; preparing 38-80 mol % of a monovinyl aromatic compound; preparing 2-45 mol % of a divinylaromatic compound; and polymerizing the bridged ring monomer compound, the monovinyl aromatic compound, and the divinylaromatic compound to form the hydrocarbon resin polymer.

[0067] Hereinafter, one or more embodiments of the present disclosure will be described in detail with reference to examples. However, these examples are only used to explain the embodiments of the present disclosure, and are not intended to limit the scope of the embodiments of the present disclosure.

[0068] Examples 1 to 39 and Comparative Example 1 Preparation of Hydrocarbon Resin Polymers

[0069] A mixture was prepared by adding a bridged ring monomer compound, a monovinyl aromatic compound, and a divinylaromatic compound to toluene in a two-neck flask in the ratios shown in Table 1 below. A catalyst shown in Table 1 was added to the mixture, and the mixture was stirred for 3 hours at the reaction temperature shown in Table 1 to polymerize the bridged ring monomer compound, the monovinyl aromatic compound, and the divinylaromatic compound. Ammonium hydroxide (NH4OH) was added to the two-neck flask to terminate the polymerization reaction. The polymer solution obtained by the polymerization reaction was dropped into isopropanol to obtain a white solid. The white solid was filtered and vacuum dried to obtain Examples 1 to 23. A commercially available SA9000 resin (polyphenylene ether resin) was used as Comparative Example 1, and the same method as in Examples 1 to 23 was used to polymerize the bridged ring monomer compound, the monovinyl aromatic compound, and the divinylaromatic compound. Examples 24 to 39 A hydrocarbon resin polymer was prepared. Examples 1 to 39 The yields of the hydrocarbon resin polymers are shown in Table 1 below. Examples 1 to 39 The hydrocarbon resin polymer of the above and the polyphenylene ether resin of Comparative Example 1 are referred to as resins.

[0070] [Table 1(1)]

[0071] [Table 1(2)]

[0072] [Table 1(3)]

[0073] [Table 1(4)]

[0074] Structure and composition analysis of hydrocarbon resin polymers

[0075] Using a nuclear magnetic resonance spectrometer (JEOL, JNM-ECZ400S), 13 C-Nuclear Magnetic Resonance (NMR) and 1 By H-NMR, Examples 7 to 17 and 23 and Examples 27, 35, 37 and 38 The structure and composition of the hydrocarbon resin polymer was analyzed, and it was confirmed that the hydrocarbon resin polymer contained repeat units from the compounds shown in Table 2. Table 2 further shows the content of each repeat unit in the hydrocarbon resin polymer. Using CDCl3 as a solvent and the resonance line of CDCl3 as an internal standard, the degree of crosslinking of the hydrocarbon resin polymer was calculated according to the following formula. The results are shown in Table 2 below.

[0076]

number

[0077] [Table 2(1)]

[0078] [Table 2(2)]

[0079] Determination of hydrogen content in reactive double bonds

[0080] Examples 1 to 39 and Comparative Example 1 The resins were dissolved in deuterated chloroform (CDCl3). Examples 1 to 39 and Comparative Example 1 The hydrogen content in the reactive double bonds of the resins was measured. Specifically, the sum of the integral values ​​of the hydrogen in the reactive double bonds was divided by the sum of the integral values ​​of all hydrogen, Examples 1 to 39 and Comparative Example 1 The hydrogen content in the reactive double bonds of the resin was determined.

[0081] Measurement of number average molecular weight (Mn) and polymer dispersity index (PDI)

[0082] Using polystyrene as a standard, gel permeation chromatography (GPC) (Waters APC, column: Waters Acquity XT 900) was performed. Examples 1 to 39 and Comparative Example 1 The number average molecular weight (Mn) and polymer dispersity index (PDI) of the resin were measured.

[0083] Tetrahydrofuran (THF) 5 mL Examples 1 to 39 and Comparative Example 1 Add 0.01g of each resin to Examples 1 to 39 and Comparative Example 1 A sample was prepared and filtered through a 0.22 μm filter. Examples 1 to 39 and Comparative Example 1 The sample was filtered and then analyzed by the instrument. Examples 1 to 39 and Comparative Example 1 The number average molecular weight (Mn) and polymer dispersity index (PDI) of the resins were obtained, respectively.

[0084] Measurement of decomposition temperature (Td) and oxidation temperature

[0085] Thermogravimetric analysis (TGA, TA / Q500) Examples 1 to 39 and Comparative Example 1 The thermal decomposition temperature (Td) and oxidation temperature of the resin were measured.

[0086] The test temperature range was from room temperature to 900°C. The heating rate was 10°C / min, and there was no nitrogen flow protection. Here, the oxidation temperature is the temperature at which the weight increases. No oxidation temperature was detected, which indicates that the oxidation temperature of the resin is very high and that the resin has very good thermal stability.

[0087] Measurement of glass transition temperature (Tg)

[0088] Dynamic mechanical analysis (DMA, TA / Q800) Examples 1 to 39 and Comparative Example 1 The glass transition temperature (Tg) of the resin was measured.

[0089] Examples 1 to 39 and Comparative Example 1 The resin was heated from 25°C to 270°C at a rate of 3°C / min. The test frequency was 1Hz. From the tan delta peak in the DMA chart, Examples 1 to 39 and Comparative Example 1 The glass transition temperature (Tg) of the resin was obtained.

[0090] Polymer morphology

[0091] When preparing the resin, ammonium hydroxide (NH4OH) was added to the two-neck flask to terminate the polymerization reaction, and the state of the reaction solution was observed with the naked eye. When the reaction solution lost fluidity, the polymer was judged to be in a gel state, which indicated that the resin had been cross-linked excessively during the polymerization reaction.

[0092] Solubility Test

[0093] Examples 1 to 39 and Comparative Example 1 1 g of each resin was added to 1 g of toluene. If the resin was completely dissolved and clear after stirring at room temperature for 3 hours, it was said that the resin passed the solubility test.

[0094] Examples 1 to 39 and Comparative Example 1 The results of the above-mentioned property measurements for this resin are shown in Table 3.

[0095] [Table 3(1)]

[0096] [Table 3(2)]

[0097] [Table 3(3)]

[0098] [Table 3(4)]

[0099] As can be seen from Table 3 above, Examples 28 to 36, 38 and 39 The hydrocarbon resin polymer of Example 1 did not pass the solubility test, whereas the hydrocarbon resin polymers of Examples 1 to 23 of the present disclosure all passed the solubility test. Examples 28 to 36, 38 and 39 This shows that the solubility of the hydrocarbon resin polymer of the present disclosure is superior to that of the hydrocarbon resin polymer of Examples 1 to 23 of the present disclosure. Furthermore, it can be seen from Table 3 that the oxidation temperatures of the hydrocarbon resin polymers of Examples 1 to 23 of the present disclosure are all high. Examples 36 to 37 Compared with the Td (1 wt% / 5 wt%) of the hydrocarbon resin polymer of Examples 1-2, 4-7, 9-10, and 12-20, the hydrocarbon resin polymers of Examples 1-2, 4-7, 9-10, and 12-20 have a Td (1 wt%) higher than 280°C and a Td (5 wt%) higher than 360°C, indicating that the hydrocarbon resin polymer of the present disclosure has excellent thermal performance and thermal stability.

[0100] Tables 1 and 3 Examples 34, 35 and 39As can be seen from Fig. 1, if the amount of the divinyl aromatic compound is too large, for example, more than 40 mol%, the resulting hydrocarbon resin polymer becomes gel-like. The formation of a gel-like polymer indicates that the reaction rate of the polymerization reaction is too fast, which is disadvantageous for the progress of the subsequent processing steps. That is, Examples 34, 35 and 39 Compared to the hydrocarbon resin polymers of the previous disclosure, the hydrocarbon resin polymers of the present disclosure have better processability.

[0101] Examples 7 and 8 of Table 2 and Table 3 12~17 As can be seen from the contents of Tables 1 to 3, the higher the ratio of repeat units from bridged ring monomer compounds + divinylaromatic compounds in the hydrocarbon resin polymer, the higher the thermal decomposition temperature of the hydrocarbon resin polymer. The hydrocarbon resin polymers of Examples 7 to 17 of the present disclosure have 13% or more repeat units from bridged ring monomer compounds + divinylaromatic compounds, which indicates that the hydrocarbon resin polymers of the present disclosure have excellent thermal performance and thermal stability. Examples 36 to 37 As can be seen from the contents of the document, the pyrolysis temperature of the hydrocarbon resin polymers that do not contain repeat units from the divinyl aromatic compound or that are formed with a relatively small amount of the divinyl aromatic compound added is low, which indicates poor thermal performance.

[0102] Electrical Performance Testing

[0103] (1) Test A

[0104] Examples 1 to 18 and 23 to 27 and Comparative Example 1 20 g of each of the resins was dissolved in 20 g of toluene to prepare a mixture. The mixture was stirred until the resin therein was completely dissolved, and the mixture was obtained as Examples 1 to 18 and 23 to 27 and Comparative Example 1 A resin solution was prepared.

[0105] Glass fiber cloth (Asahi 2116, Dk / Df=3.3 / 0.0030 at 28 GHz) was used in Examples 1 to 18 and 23 to 27 and Comparative Example 1The resin solutions of Examples 1 to 18 and 23 to 27 and Comparative Example 1 The sample was prepared as follows. Using network analyzer software (network analyzer Keysight, P5007A, SCR), the Dk / Df and RC% of the sample at 28 GHz were measured. The results are shown in Table 4 below. After baking the sample at 170°C for 10 minutes, the Dk / Df and RC% of the sample at 28 GHz were measured again. The results are shown in Table 4 below. Here, RC% indicates the resin content. RC% = (weight after baking - weight of glass cloth) / weight after baking * 100%.

[0106] [Table 4]

[0107] As can be seen from Table 4 above, Examples 24 to 27 After baking at 170℃ for 10 minutes, the Df value of the hydrocarbon resin polymer increases obviously, and the Df value of the hydrocarbon resin polymer exceeds 0.0020. The above results show that: Examples 24 to 27 Compared with the hydrocarbon resin polymer of the present disclosure, the hydrocarbon resin polymer of the present disclosure shows better thermal stability, and therefore the hydrocarbon resin polymer of the present disclosure can retain excellent electrical performance after the heating process.

[0108] (2) Test B

[0109] 100 parts by weight of the hydrocarbon resin polymer of Example 1, 50 parts by weight of a toughening agent (Ricon 100, purchased from Cray Valley), 1 part by weight of an initiator (Perbutyl P, purchased from NOF), and 35 parts by weight of a crosslinking agent (TAIC, purchased from Cray Valley) were dissolved in 100 parts by weight of toluene to form a mixture. The mixture was stirred until the hydrocarbon resin polymer, toughening agent, initiator, and crosslinking agent therein were completely dissolved to form a composition solution of Example 1. The hydrocarbon resin polymer of Example 1 was dissolved in the same manner as in Examples 2-7, 9-11, 13, and 19. , 20, 26 and 27 and Comparative Example 1 Using the same method, Examples 2 to 7, 9 to 11, 13, and 19 were used instead of the resin. , 20, 26 and 27 and Comparative Example 1 A composition solution was prepared.

[0110] Glass fiber cloth (Asahi 2116, Dk / Df=3.3 / 0.0030 at 28 GHz) was used in Examples 1 to 7, 9 to 11, 13, and 19. , 20, 26 and 27 and Comparative Example 1 The compositions of Examples 1 to 7, 9 to 11, 13, and 19 were immersed in the respective compositions. , 20, 26 and 27 and Comparative Example 1 The composition sample was baked at 160°C for 7 minutes, and then the Dk / Df and RC% of the composition sample at 28GHz were measured using a network analyzer software (network analyzer Keysight, P5007A, SCR). The results are shown in Table 5.

[0111] [Table 5]

[0112] As can be seen from Table 5 above, the resin compositions formed by combining the hydrocarbon resin polymers of Examples 1-7, 9-11, 13, 19 and 20 with the toughening agent, initiator, and crosslinking agent, etc., have extremely good Df after baking at 160°C, for example, less than 0.0024, and even less than 0.0020. Thus, the resin compositions of the present disclosure have excellent electrical performance even after the heating process.

[0113] (3) Test C

[0114] A mixture was made by mixing 100 parts by weight of the hydrocarbon resin polymer of Example 1, 50 parts by weight of a toughening agent (Ricon 100, purchased from cray valley), 1 part by weight of an initiator (Perbutyl P, purchased from NOF), 35 parts by weight of a crosslinking agent (TAIC, purchased from cray valley), and a filler (SVC, purchased from Admatch or SS-10, purchased from Tokuyama) with 100 parts by weight of toluene. The filler was ground with zirconium beads until it was uniformly dispersed in the mixture to make the polymer solution of Example 1. Two pieces of glass fiber cloth (Asahi 2116, Dk / Df=3.3 / 0.0030 at 28 GHz) were immersed in the polymer solution of Example 1 and baked at 160° C. for 7 minutes to make two polymer layers. The two polymer layers and a copper foil layer were laminated together. Copper foil was placed between these two polymer layers, and a silane adhesive (KBM503) was used to connect the copper foil and the polymer layers to form the laminate structure of Example 1. A pressure of 400 PSI was applied to the laminate structure of Example 1 at a temperature of 210°C for 1 hour to complete the fabrication of the substrate sample of Example 1.

[0115] The hydrocarbon resin polymer of Example 1 was mixed with the hydrocarbon resin polymer of Examples 2, 4 to 7, 9 to 11, and 13 to 20. , 22 and 27 and Comparative Example 1 After replacing the resin with that of Examples 2, 4 to 7, 9 to 11, and 13 to 20, the same procedure was used. , 22 and 27 and Comparative Example 1 A substrate sample was made. The Dk / Df of the substrate sample was measured at 28 GHz using a network analyzer software (network analyzer Keysight, P5007A, SCR). The results are shown in Table 6.

[0116] [Table 6]

[0117] As can be seen from Table 6 above, the substrate samples of the present disclosure had excellent electrical performance, such as Df less than 0.0032, and even less than 0.0025.

[0118] [Peel strength test]

[0119] A mixture was made by mixing 100 parts by weight of the hydrocarbon resin polymer of Example 8, 25 parts by weight of a toughening agent (Ricon 100, purchased from cray valley), 1 part by weight of an initiator (Perbutyl P, purchased from NOF), 15 parts by weight of a crosslinker (TAIC, purchased from cray valley), and 30 parts by weight of a filler (SVC, purchased from Admatch or SS-10, purchased from Tokuyama) with 100 parts by weight of toluene. The filler was ground with zirconium beads until it was uniformly dispersed in the mixture to make the polymer solution of Example 8. Four pieces of glass fiber cloth (Asahi 2116, Dk / Df=3.3 / 0.0030 at 28 GHz) were immersed in the polymer solution of Example 8 and baked at 160° C. for 7 minutes to make four polymer layers. A silane adhesive (KBM503) was applied to the surface of the copper foil layer, and the four polymer layers and copper foil were laminated together. The copper foil was then placed between the four polymer layers and pressed to form a laminate structure sample of Example 8.

[0120] The hydrocarbon resin polymer of Example 8 was replaced with the hydrocarbon resin polymer of Examples 14 to 17, and the laminated structure samples of Examples 14 to 17 were formed in the same manner. The sample width of the laminated structure samples of Examples 8 and 14 to 17 was 12.7 mm. The peel strength of the laminated structure samples was measured using a tensile tester (SHIMADZU AG-Xplus, test conditions: test speed 50.8 mm / min, test length: 20 mm). The obtained results are shown in Table 7 below.

[0121] [Table 7]

[0122] As can be seen from the contents of Table 7 above, the lower the hydrogen content in the reactive double bond of the hydrocarbon resin polymer, the lower the peel strength. Specifically, the hydrogen content in the reactive double bond of the hydrocarbon resin polymer of Example 17 is low (2%), and its peel strength is low (0.89 lb / in). Therefore, in some embodiments, the hydrogen content in the reactive double bond in the hydrocarbon resin polymer is preferably higher than 2.2%, and preferably 2.2% to 10%. Therefore, the hydrocarbon resin polymer has excellent thermal stability and electrical performance, and the substrate containing the hydrocarbon resin polymer can have high peel strength and reliability.

[0123] As can be seen from the above-mentioned various tests, the hydrocarbon resin polymer of the present disclosure prepared using the method for preparing the hydrocarbon resin polymer of the present disclosure has excellent thermal performance, thermal stability, electrical performance, solubility and / or processability. The hydrocarbon resin polymer of the present disclosure maintains excellent electrical performance after the heating process and / or heat pressing process, and is cost-effective. The resin composition containing the hydrocarbon resin polymer of the present disclosure has excellent thermal performance, thermal stability, electrical performance and / or processability. The substrate containing the hydrocarbon resin polymer of the present disclosure also has excellent thermal performance, thermal stability and / or electrical performance.

[0124] The features of the above-mentioned embodiments are useful for those skilled in the art to understand the present invention. Those skilled in the art should understand that other processes and structures can be designed and modified based on the present invention to achieve the same purpose and / or the same advantages as the above-mentioned embodiments. Those skilled in the art should also understand that these equivalent replacements do not depart from the spirit and scope of the present invention, and can be modified, changed or altered without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0125] 10...Substrate 101...Bass 103…coincident layer 105…Next layer

Claims

1. 0.15 to 15 mol % of a repeating unit (A) derived from a bridged ring monomer compound; 15 to 90 mol % of a repeating unit (B) derived from a monovinyl aromatic compound; 8 to 80 mol % of a repeating unit (C) derived from a divinyl aromatic compound; A hydrocarbon resin polymer comprising: The bridged ring monomer compound is a compound containing a bridged ring structure, The bridged ring structure is a structure containing at least two carbon rings therein, and the at least two carbon rings share two carbon atoms that are not directly linked to each other. The hydrocarbon resin polymer is measured by NMR, and the sum of the integral values ​​of hydrogen of reactive double bonds is divided by the sum of the integral values ​​of all hydrogen. A hydrocarbon resin polymer, wherein the hydrogen content in the reactive double bonds of said hydrocarbon resin polymer is less than 10%.

2. 2. The hydrocarbon resin polymer of claim 1, wherein said bridged ring monomer compound comprises said bridged ring structure, said bridged ring structure comprising from 3 to 12 ring atoms and from 1 to 2 double bonds.

3. At least one hydrogen atom in the bridged ring structure is 1-20 Alkyl group, C 2-20 Alkenyl group, or C 1-20 3. The hydrocarbon resin polymer according to claim 2, which is substituted with at least one substituent selected from the group consisting of carboxylate groups having alkyl chains.

4. At least two hydrogen atoms in the bridged ring structure are 1-20 Alkyl group, C 2-20 Alkenyl group, or C 1-20 4. The hydrocarbon resin polymer according to claim 3, which is substituted with at least two substituents selected from the group consisting of carboxylate groups having alkyl chains, and said at least two substituents form a ring.

5. 2. The hydrocarbon resin polymer according to claim 1, wherein the bridged ring monomer compound is at least one selected from the group consisting of norbornene (NB), dicyclopentadiene (DCPD), dicycloheptadiene (NBD), 2-acetyl-5-norbornene, vinyl norbornene, and ethylidene-norbornene.

6. 2. The hydrocarbon resin polymer according to claim 1, wherein the total amount of said repeating units (A) and said repeating units (C) in said hydrocarbon resin polymer is 13 mol % or more.

7. The hydrocarbon resin polymer according to claim 1, wherein the hydrocarbon resin polymer contains 3 to 12 mol % of the repeating unit (A).

8. The hydrocarbon resin polymer according to claim 1, wherein the hydrocarbon resin polymer contains 25 to 85 mol % of the repeating unit (B).

9. The hydrocarbon resin polymer according to claim 1, wherein the hydrocarbon resin polymer contains 10 to 75 mol % of the repeating unit (C).

10. 2. The hydrocarbon resin polymer according to claim 1, wherein the degree of crosslinking of the repeating unit (C) in the hydrocarbon resin polymer is 0.2 to 0.

6.

11. The hydrocarbon resin polymer of claim 1, wherein the number average molecular weight (Mn) of the hydrocarbon resin polymer is 2,500 to 10,000 g / mol.

12. 1. A method for making a hydrocarbon resin polymer, comprising: providing 15-40 mol % of a bridged ring monomer compound; providing 38-80 mol % of a monovinyl aromatic compound; providing 2-45 mol % of a divinyl aromatic compound; BF 3 ・OEt 2 providing a catalyst consisting of: polymerizing said bridged ring monomer compound, said monovinyl aromatic compound, and said divinyl aromatic compound to form said hydrocarbon resin polymer; 1. A method for making a hydrocarbon resin polymer comprising: The bridged ring monomer compound is a compound containing a bridged ring structure, The bridged ring structure is a structure containing at least two carbon rings therein, and the at least two carbon rings share two carbon atoms that are not directly linked to each other.

13. A resin composition comprising a hydrocarbon resin polymer, the hydrocarbon resin polymer comprising: 0.15 to 15 mol % of a repeating unit (A) derived from a bridged ring monomer compound; 15 to 90 mol % of a repeating unit (B) derived from a monovinyl aromatic compound; 8 to 80 mol % of a repeating unit (C) derived from a divinyl aromatic compound; A resin composition comprising: The bridged ring monomer compound is a compound containing a bridged ring structure, The bridged ring structure is a structure containing at least two carbon rings therein, and the at least two carbon rings share two carbon atoms that are not directly linked to each other. The hydrocarbon resin polymer is measured by NMR, and the sum of the integral values ​​of hydrogen of reactive double bonds is divided by the sum of the integral values ​​of all hydrogen. A resin composition, wherein the hydrogen content in the reactive double bonds of said hydrocarbon resin polymer is less than 10%.

14. The resin composition according to claim 13, further comprising another resin polymer, wherein the weight ratio of said hydrocarbon resin polymer to said another resin polymer is 100-1:0-99.

15. The resin composition according to claim 14, wherein the other resin polymer comprises a polyphenylene ether resin, a polycarbonate resin, an acrylic resin, an epoxy resin, a polyurethane resin, or any combination thereof.

16. 14. The resin composition of claim 13, further comprising an initiator, a crosslinker, an additive, or any combination thereof.

17. A substrate comprising a hydrocarbon resin polymer, the hydrocarbon resin polymer comprising: 0.15 to 15 mol % of a repeating unit (A) derived from a bridged ring monomer compound; 15 to 90 mol % of a repeating unit (B) derived from a monovinyl aromatic compound; 8 to 80 mol % of a repeating unit (C) derived from a divinyl aromatic compound; A substrate comprising: The bridged ring monomer compound is a compound containing a bridged ring structure, The bridged ring structure is a structure containing at least two carbon rings therein, and the at least two carbon rings share two carbon atoms that are not directly linked to each other. The hydrocarbon resin polymer is measured by NMR, and the sum of the integral values ​​of hydrogen of reactive double bonds is divided by the sum of the integral values ​​of all hydrogen. A substrate, wherein the hydrogen content in the reactive double bonds of said hydrocarbon resin polymer is less than 10%.

18. 18. The substrate according to claim 17, further comprising another resin polymer, wherein the weight ratio of said hydrocarbon resin polymer to said another resin polymer is 100-1:0-99.

19. With the base, a polymer layer disposed over the base; an adhesive layer disposed between the base and the polymer layer; Including, The substrate of claim 17 , wherein the polymer layer comprises the hydrocarbon resin polymer.

Citation Information

Patent Citations

  • Soluble polyfunctional vinyl aromatic copolymer, method for producing the same, curable resin composition, and cured product of the same

    JP2018039995A

  • Curable resin composition, cured product of the same, curable composite material, metal foil with resin, and varnish for circuit board material

    JP2018168347A

  • Curable resin composition, prepreg, metal-clad laminate, and printed wiring board

    WO2021166649A1